What Research Shows about Mathematics Teachers’ Learning Needs: Experience from Latvia - France, Ilze; Namsone, Dace; Cakane, Liga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The implementation of new skills (competencies) according to education regulation documents in 2006 – 2008 demanded a change in the Mathematics and Science teaching practice in Latvia. Work on the new education reform started this year (2015). The aim of the research is to look for the answers to the following questions – do the changes in learning approach occur and are teachers’ skills sufficient for organizing a different teaching process? What are the learning needs expressed by teachers and concluded by experts? The range of cognitive activity, collaboration and focusing on students’ learning are the criteria set for lesson observations. The research shows a tendency that changes envisioned in education policy resolutions fail to be reflected in school practice. In many cases, the demonstrated teachers’ instructional skills were insufficient. The research shows the clear need to improve the instructional skills - to develop higher order cognitive skills (HOCS) oriented learning activities, to organize students’ collaboration etc. The research proves the existence of the need to improve teachers’ reflection skills and points to the deep contradiction between teachers’ performance in the classroom and their own understanding about it.